2023
DOI: 10.1111/apa.16939
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effect of early and prolonged kangaroo mother care on long‐term neuro‐developmental outcomes in low birth neonates – A cohort study

Shridevi Bisanalli,
Bharathi Balachander,
A. Shashidhar
et al.

Abstract: AimKangaroo mother care(KMC) has immense short‐term benefits, but data on long‐term outcomes is scarce. Hence this study aimed to compare the neurodevelopmental outcomes at 12 months of corrected age (CA) in infants <2000 g receiving early and prolonged KMC to a control group.MethodsThis was a cohort study that was conducted from January 2017 to November 2018. All neonates< 2000g were eligible for the study. Neonates that received early initiation (<72 hours of life) and prolonged KMC comprised the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…There are findings that show how KMC has contributed to enhancing the health of infants in the community and in hospitals [16]. Pradhan et al evaluated the applicability of KMC as a complementary treatment in the hospital setting [23], while Ariff et al [3] and Bisanalli et al [13] examined the role of KMC in rural populations in the community setting, with results showing favorable outcomes for newborns in the longer term.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are findings that show how KMC has contributed to enhancing the health of infants in the community and in hospitals [16]. Pradhan et al evaluated the applicability of KMC as a complementary treatment in the hospital setting [23], while Ariff et al [3] and Bisanalli et al [13] examined the role of KMC in rural populations in the community setting, with results showing favorable outcomes for newborns in the longer term.…”
Section: Discussionmentioning
confidence: 99%
“…While skin-to-skin contact strengthens the bond between mother and child, involving the family and men will further strengthen it [ 19 , 20 ]. Bisanalli et al's study showed that the beneficial effect of early and prolonged effective KMC on neurodevelopmental outcomes in late preterm and low-birthweight babies at later times is significant [ 13 ]. Their review explored the neurodevelopmental outcomes of KMC over an extended period, which brought up a lot of important information concerning the long-term benefits of KMC for late preterm neonates and clinical practice, and guidelines on the implementation of KMC in neonatal wards in care settings was one of them [ 13 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations